Clinical evaluation and comparison of the efficacy of coronally advanced flap alone and in combination with platelet rich fibrin membrane in the treatment of Miller Class I and II gingival recessions - Santosh Gupta; Ruchi Banthia; Pallavi Singh; Priyank Banthia; Sapna Raje; Neha Aggarwal (Wolters Kluwer Medknow Publications, 2015)
Background: The aim of this study was to compare the clinical efficacy of coronally advanced flap (CAF) alone and in combination with autologous platelet rich fibrin membrane (PRF) in Miller's class I and II gingival recessions. Materials and Method: Thirty isolated Miller class I or II sites in 26 subjects were randomly divided into test (15 sites- CAF+PRF) and control (15 sites- CAF alone). Parameters probing pocket depth (PPD), Recession depth (RD), Clinical attachment loss (CAL), Keratinised tissue width (KTW) and Gingival tissue thickness (GTH) were evaluated at baseline, 3 months and 6 months postoperatively. Data was subjected to statistical analysis. P< 0.05 was considered statistically significant. Results: Mean percentage root coverage was 91.00±19.98% and 86.60±23.83% for test and control group respectively. Difference between the groups in all parameters at baseline, 3 months and 6 months was non significant. Complete root coverage was obtained in 12 (80%) and 11 (73.3%) subjects in test and control group respectively. The difference was found to be non-significant. Both groups showed significant differences in all parameters at 3 and 6 months respectively except difference in gingival tissue thickness which was non-significant in control group at 3 months. Conclusion: Combination of PRF to CAF procedure did not provide any added advantage in term of recession coverage in Miller class I and II recessions. Long term trials with more sample size are needed to validate these findings.